Fungi found in association with discoloured wood of kiwifruit vines in New Zealand - Tyson, Joy L.; Mellow, Kieran D. (New Zealand Plant Protection, 2024)
Vine decline and trunk diseases have been observed in New Zealand kiwifruit orchards since the year 2000. In 2019, a block of Actinidia chinensis var. deliciosa ‘Hayward’ vines that were being re-grafted was noted to have differences in colouration of the internal wood of the cut trunks, with dark cores often corresponding with less vigorous vines and/or vines with trunk disorders. Cross-sections of 10 symptomatic and 10 externally asymptomatic trunks were taken from 1–1.5 m above the soil and fungal isolations made across the width of the trunks. Fungi found within the symptomatic vines included Neobulgaria alba, Ilyonectria spp., Neonectria microconidia, Gliomastix murorum, Clonostachys sp. and Penicillium sp. There was a wide variety of symptoms and fungal profiles seen. However, Neobulgaria alba often closely matched the stained areas seen in the wood and was not recovered from the asymptomatic vines. The most common fungus in the asymptomatic vines was Chaetomium sp. These isolations revealed a group of fungal genera that were associated with diseased trunks of kiwifruit at this site. Pathogenicity testing is needed to confirm which of these fungi are secondary invaders and which are primary pathogens of this host.